2010
DOI: 10.1103/physreve.81.030102
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries shape the current in ratchets induced by a biharmonic driving force

Abstract: Equations describing the evolution of particles, solitons, or localized structures, driven by a zero-average, periodic, external force, and invariant under time reversal and a half-period time shift, exhibit a ratchet current when the driving force breaks these symmetries. The biharmonic force f͑t͒ = ⑀ 1 cos͑qt + 1 ͒ + ⑀ 2 cos͑pt + 2 ͒ does it for almost any choice of 1 and 2 , provided p and q are two coprime integers such that p + q is odd. It has been widely observed, in experiments in semiconductors, in Jo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
66
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 38 publications
7
66
1
Order By: Relevance
“…As shown in Ref. [11], the functional form in Eq. (14) is a consequence solely of the system symmetries, being independent of the interaction details.…”
Section: Model-specific Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Ref. [11], the functional form in Eq. (14) is a consequence solely of the system symmetries, being independent of the interaction details.…”
Section: Model-specific Examplesmentioning
confidence: 99%
“…(12), and satisfies the conditions imposed by Eqs. (10) and (11). It is to be noted that, in this figure,V ω 2,0 (0) =V (ω 2,0 ,0) = λ/T 0 , where T 0 = 2πq 0 /ω 1 = 6π/ω 1 is the period of the biharmonic force (see Ref.…”
Section: Model-specific Examplesmentioning
confidence: 99%
“…For no dissipation (Hamiltonian case), the system is symmetric under time reversal for φ = nπ with n integer, and therefore for these values directed motion cannot be produced. It can be shown [9,23] that the dependence of the average velocity on the phase φ is, in leading order, v = A sin φ. Consider now the case of nonzero dissipation.…”
Section: B Symmetry Analysismentioning
confidence: 99%
“…Thus, a current can be generated also for these values of the phase φ. For weak dissipation, the dependence of the average velocity on the phase φ is, in leading order, v = A sin(φ − φ 0 ), where φ 0 is a dissipation-induced symmetry-breaking phase lag which vanishes in the Hamiltonian limit [10,23,24]. Finally, in the overdamped regime, the system is invariant under the so-called supersymmetry [11] (x,p,t) → (x + λ/2, − p, − t), with λ the spatial period of the potential, for φ = π/2 + nπ , with n integer.…”
Section: B Symmetry Analysismentioning
confidence: 99%
“…Time or space periodicity is reflected in the properties of these systems through a dependence on the parameters of their periodic terms [1,2]. In this talk, it is shown that simple symmetry considerations determine how their properties depend functionally on the amplitudes and the phases of the periodic terms, regardless of whether they are classical or quantum, stochastic or deterministic, dissipative or nondissipative [3].…”
mentioning
confidence: 99%